Проблеми регулювання міжнародних резервів і платіжного балансу України - Веріга, Г.В. (Культура народов Причерноморья, 2013)
Розглянуто призначення, теоретичні основи регулювання міжнародних резервів.
Проаналізовано динаміку офіційних валютних резервів і платіжного балансу України протягом
десятирічного періоду, формалізовано взаємозв’язок між ними. Надано оцінку складу національних
міжнародних резервів, джерелам їх наповнення і напрямам використання на предмет відповідності
міжнародним стандартам. Виділено етапи процесу розбудови механізму управління золотовалютними
резервами. Обґрунтовано напрями розвитку форм і методів регулювання міжнародних резервів і
платіжного балансу України.
Ключові слова: міжнародні резерви, платіжний баланс, регулювання, склад, динаміка Рассмотрено назначение, теоретические основы регулирования международных резервов.
Проанализирована динамика официальных валютных резервов и платежного баланса Украины в
течение десятилетнего периода, формализирована взаимосвязь между ними. Дана оценка составу
национальных международных резервов, источникам их наполнения и направлениям использования на
предмет соответствия международным стандартам. Обоснованы направления развития форм и
методов регулирования международных резервов и платежного баланса Украины.
Ключевые слова: международные резервы, платежный баланс, регулирование, состав, динамика Theoretical basis and functions of international reserves regulation were considered. The dynamics
of official currency reserves and a balance of payments in Ukraine during a ten-year period were analyzed; an
interconnection between them was formalized. The content of national international reserves, sources of filling
them in and ways of their usage were tested for accordance to international standards. Main sources of forming
official currency reserves were determined, e.g. mandatory currency sale to exporters, interventional NBU
transactions (purchase of currency on an interbank market), IMF tranches, external and internal loans in a
foreign currency. Currency interventions (sale of international currency) are a basic course of using official
monetary reserves. Their main goal is to restrain national currency rate depreciation in conditions of negative
balance of current account. Financial instruments which conduct official currency reserves, e.g. governmental
securities with fixed yield of the highest investment grade and short-term deposits in non-residential banks were
systematized. Basic ways of improvement of the control on gold coin reserves of the NBU, e.g. diversification
expansion, portfolio management, profitability and risk optimization were determined.
Key words: international reserves, balance of payment, regulation, content, dynamics.